2000
DOI: 10.1021/jm990615a
|View full text |Cite
|
Sign up to set email alerts
|

3,5-Bis(trifluoromethyl)pyrazoles:  A Novel Class of NFAT Transcription Factor Regulator

Abstract: A series of bis(trifluoromethyl)pyrazoles (BTPs) has been found to be a novel inhibitor of cytokine production. Identified initially as inhibitors of IL-2 synthesis, the BTPs have been optimized in this regard and even inhibit IL-2 production with a 10-fold enhancement over cyclosporine in an ex vivo assay. Additionally, the BTPs show inhibition of IL-4, IL-5, IL-8, and eotaxin production. Unlike the IL-2 inhibitors, cyclosporine and FK506, the BTPs do not directly inhibit the dephosphorylation of NFAT by calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(67 citation statements)
references
References 21 publications
1
66
0
Order By: Relevance
“…We have previously reported the chemical synthesis and optimization of the bistrifluoromethyl pyrazole series of cytokine inhibitors with respect to bioavailability, half-life, and efficacy to inhibit IL-2 synthesis in rodents and nonhuman primates (32). This report extends these findings by providing evidence that the BTP compounds work at the level of NFAT regulation.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…We have previously reported the chemical synthesis and optimization of the bistrifluoromethyl pyrazole series of cytokine inhibitors with respect to bioavailability, half-life, and efficacy to inhibit IL-2 synthesis in rodents and nonhuman primates (32). This report extends these findings by providing evidence that the BTP compounds work at the level of NFAT regulation.…”
Section: Discussionsupporting
confidence: 52%
“…As shown in Fig. 9, A, phosphorylated Elk-1c (pElk-1) is dephosphorylated (as measured by a decrease in 32 P content and an increase in electrophoretic mobility) when incubated with COS-7 cell lysate. The dephosphorylation of pElk-1 is inhibited in a dosedependent fashion by the addition of CsA or EGTA to the cell lysates (Fig.…”
Section: Btp Compounds Fail To Inhibit Can Activity In Cellmentioning
confidence: 81%
See 1 more Smart Citation
“…BTPs were originally identified as inhibitors of T lymphocyte activation (24). Several reports have suggested that BTP2 (Pyr2) is a potent inhibitor for both Ca 2ϩ release-activated Ca 2ϩ (CRAC) channels and TRPC channels and for NFAT-driven IL-2 production (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Bis(trifluoromethyl)pyrazoles (BTPs) are a class of pyrazole derivatives that act as potent immunosuppressive compounds by inhibiting cytokine release from human lymphocytes and suppressing T cell proliferation (24). The BTP derivative 4-methyl-4Ј-[3,5-bis(trif luoromethyl)-1H-pyrazol-1-yl]-1,2,3-thiadiazole-5-carboxanilide, BTP2 (YM-58483), was shown to block SOCs in T lymphocytes and TRPC channels in HEK293 cells (25)(26)(27).…”
Section: Canonical Transient Receptor Potential (Trpc) Channels Contrmentioning
confidence: 99%